Kedudukan Hukum PT. Inter Sport Marketing Sebagai Pemegang Lisensi Hak Cipta Piala Dunia Tahun 2014 Terhadap Penyiaran Piala Dunia Tidak Berizin oleh Pihak Ketiga - Kanza Latunhi Rayes (Fakultas Hukum Universitas Islam Indonesia, 2020)
PT. Inter Sport Marketing (PT. ISM) becomes one of the licensees permission from FIFA to serve the World Cup broadcasts throughout the territory of the Republic of Indonesia, which has been created and signed through the license agreement date 5 May 2011 between PT. ISM with FIFA. The license agreement makes PT. ISM to be Master Rights Holder of the media rights. Nevertheless, there have been pros and cons that come down into two core problems. First, the legal standing of PT. ISM which is doubtful by various parties is even deemed to have no legal capacit. Second, the legal consequences of the license agreement itself on the third party, especially for the parties who do not get the World Cup broadcast permit from the 2014 official licensee; The purpose of this research is to know the legal position of PT. ISM as a copyright licensee and the legal consequences of licensing agreements between the parties of PT. ISM and FIFA against third parties; This research includes normative law with a conceptual approach that is based on legislation, doctrine, and jurisprudence, with the method of retrieving literature study data; this research concludes that PT. ISM has a legal position or legal capacity to prohibit anyone or any party that is detrimental to the right in the entire commercial area of the Republic of Indonesia. Under the license Agreement of FIFA is known to be legitimate, the license agreement has a legal consequence to a third party that is interpreted as the parties outside of the aforementioned agreement.